Ascorbate peroxidase‐mediated in situ labelling of proteins in secreted exosomes. Issue 6 (18th June 2022) - Lee, Byung Rho; Lee, Tae Jin; Oh, Sekyung; Li, Chenglong; Song, Jin‐Hyuk A; Marshall, Brendan; Zhi, Wenbo; Kwon, Sang‐Ho
Abstract: The extracellular vesicle exosome mediates intercellular communication by transporting macromolecules such as proteins and ribonucleic acids (RNAs). Determining cargo contents with high accuracy will help decipher the biological processes that exosomes mediate in various contexts. Existing methods for probing exosome cargo molecules rely on a prior exosome isolation procedure. Here we report an in situ labelling approach for exosome cargo identification, which bypasses the exosome isolation steps. In this methodology, a variant of the engineered ascorbate peroxidase APEX, fused to an exosome cargo protein such as CD63, is expressed specifically in exosome‐generating vesicles in live cells or in secreted exosomes in the conditioned medium, to induce biotinylation of the proteins in the vicinity of the APEX variant for a short period of time. Mass spectrometry analysis of the proteins biotinylated by this approach in exosomes secreted by kidney proximal tubule‐derived cells reveals that oxidative stress can cause ribosomal proteins to accumulate in an exosome subpopulation that contains the CD63‐fused APEX variant.